2022
DOI: 10.1080/13510002.2022.2116551
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin ameliorates oxidative glutamate testicular toxicity in rats via central and peripheral mechanisms involving SIRT1 activation

Abstract: Objectives This study aimed to evaluate the potential mitigating effect of fisetin on monosodium glutamate (MSG)-induced testicular toxicity and investigate the possible involvement of silent mating type information regulation 2 homolog 1 (SIRT1) in this effect. Methods Forty male rats were divided into normal control, fisetin-treated, MSG-treated, and fisetin + MSG-treated groups. Testosterone, GnRH, FSH, and LH were measured in plasma, as well as SIRT1 and phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Sirt1 plays a crucial role during postovulatory oocyte aging [ 17 , 18 ] and has been shown to be upregulated by fisetin [ 25 , 26 ]. However, it is unknown whether fisetin can affect Sirt1 expression in oocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirt1 plays a crucial role during postovulatory oocyte aging [ 17 , 18 ] and has been shown to be upregulated by fisetin [ 25 , 26 ]. However, it is unknown whether fisetin can affect Sirt1 expression in oocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Sirt1 may exert protective functions by regulating histone acetylation in oocytes. Fisetin can inhibit IL-1β-induced inflammatory responses, oxidative stress, and hepatic steatosis in humans and mice by increasing SIRT1 activity [ 25 , 26 , 27 ]. However, it is still unknown whether fisetin affects Sirt1 in oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Fis has been tested as an activator of SIRT1, and the effects on SIRT1 have been found in many studies 38,39 . A recent study found that Fis activates SIRT1 to ameliorate oxidative glutamate testicular toxicity 40 . Also, it has been reported that Fis ameliorates alcohol‐induced liver injury by regulating SIRT1 41 .…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 A recent study found that Fis activates SIRT1 to ameliorate oxidative glutamate testicular toxicity. 40 Also, it has been reported that Fis ameliorates alcohol‐induced liver injury by regulating SIRT1. 41 However, the potential protective effects of Fis on NPMSCs are unclear, and the mechanism of Fis function in NPMSCs is significant for us to research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fisetin, as an activator of SIRT1, prevented germ cells from apoptosis caused by hydrogen peroxide. This effect was possibly achieved by the degradation of the transcription factor FOXO3a, which is the inductor of apoptosis [ 167 ]. The abovementioned studies allow us to imply that fisetin can lower the risk of oxidative stress-related degenerative diseases [ 168 ] and metabolic syndrome with its potential for the suppression of fat accumulation in obesity [ 162 ].…”
Section: Fisetinmentioning
confidence: 99%